Desenvolvimento de um sistema capacitivo para medição de umidade de sementes embarcado em uma colhedora - Lagares Júnior, Moisés Luiz (2009)
The aim of this research was to develop a seed moisture measurement system (M.M.S.) prototype that could be embedded on a combine to harvest and analyze experimental plots. It must be able to reach the claims of seed research companies. This kind of system is trade available, though there is no technology designed in Brazil and it is imported in a high cost. To reach the aim, seven construction requirement were defined. The M.M.S. was designed and constructed obeying such requirements. Fixed frequency in 10 kHz, its operation distinguishes itself by gathering constructive characteristics capacitive sensors of parallel plates as well as concentric cylinders. Its calibration was performed using corn seeds (Zea mays L.) artificially moistened through methodology that was preliminarily developed. The calibration curve was obtained by the correlation between the sensor output voltage and the moisture seed sample. Modeling (estimated by Linear Least Squares Fitting technique and evaluated by analysis of variance) consists of three lines which delimit three reading bands (selected automatically by system). The total M.M.S. reading extends from 10 to 30 %. The system checking was comprised by comparing the prototype results to results obtained by standard oven method and three other indirect measurement methods. Thus, the prototype was achieved through the construction of a moisture measurement system that attends the construction requirements, using automatic reading temperature correction and taking into account all the conditions to be embedded on combines.